Influência de agente externo no desenvolvimento de capacidades operacionais nas cadeias de suprimentos - Vasconcelos Neto, Antonio Genesio (2017)
This research aims to verify how Supply Chain Operational Capabilities are developed from technologies (resources) of an external agent. For this, we intended to analyze the changes or improvements in Practices and Operational Capabilities in the links of the Supply Chain, from the use of technologies, transferred by technological knowledge business services (T-KIBS), as well as the impact that these technologies and operational changes may result in Operational Performance. The theoretical framework focuses on the process of developing Operational Capabilities based on changes in Operational Practices. As qualitative metolodigy for data collection, the case study was used, through semi-structured interviews. Thus, 73 companies and two focus groups, belonging to 17 links, from three Agroindustrial Supply Chains from two countries were researched. As a conditioning, was the use of technologies, transferred by an external company to the Supply Chain, used as operational resources, inducing operational changes. The results were verified according to changes that the technologies induced in the Operational Parameters (Practices, Capacities and Performance), both for the links and for the Supply Chains. Finally, we present research propositions about the influences that the implementation of T-KIBS technologies can cause in the Operational Parameters of the links and Supply Chains, varying according to the operational strategies of the companies, the position of adopting links in relation to the Chains (upstream or downstream), as well as the level of structuring of the chains, the time the technologies were adopted and the need to create new links due to the use of the technologies.